Comparison between radiation efficiencies of phone antennas and radiated power of mobile phones measured in anechoic chambers and reverberation chamber - Serafimov, N.; Kildal, P.-S.; Bolin, T. (IEEE Antennas and Propagation Society International Symposium 2002, 2002)
Chalmers University and Bluetest AB have developed a reverberation chamber that can be used to measure radiation efficiency of phone antennas and the radiated power of mobile phones. This paper describes the verification of the reverberation chamber measurements by comparison with two anechoic chambers. The total radiated power of each of ten different mobile phone models was measured. In addition, the antennas on eight of the phone models were fed by a cable (spare set of phones), and the radiation efficiencies were measured. Both the antenna radiation efficiency and the radiated power were measured in the presence of a head-and-shoulder phantom. The handsets were measured in only one position - the so-called left talk, 45/spl deg/ user-intended position. The phone tests were performed in the GSM 900 (GSM), GSM 1800 (DCS) and GSM 1900 (PCS) bands. There exists high correlation in the results of the radiation efficiencies and radiated power measured in the reverberation chamber and two different anechoic chambers, respectively. The agreement between the results of corresponding active and cable-fed devices is also good. Frequency stirring, platform stirring and polarization stirring are important for achieving accuracy when measuring in the reverberation chamber.